Ecological Policy in the Sverdlovsk Region: Problem of Improving Instruments - M. A. Feldman; A. A. Timin (Управленческое консультирование)
Goal. Analysis of the results of working by regional authorities in the field of ecology. Methods. Based on systemic approach to analyze the annual reports on the state of the environment 2003–2016. Results. Revealed that dynamics of decline of pollution of the environment is increases, for waste management positive dynamics is absent. In addition, because of low cost and inadequate use of instruments the level of environmental tension remains high. Scientific novelty. The estimation of different directions of ecological policy: degree of effectiveness of instruments, recommendations for the introduction of new.